Thalamic Structural Connectivity Abnormalities in Minimal Hepatic Encephalopathy - Chen, Hua-Jun; Zhang, Xiao-Hong; Shi, Jia-Yan; Jiang, Shao-Fan; Sun, Yi-Fan; Zhang, Ling; Li, Dan; Chen, Rong (Frontiers in Neuroanatomy, 2021)
Background & Aims: Numerous studies have demonstrated thalamus-related structural, functional, and metabolic abnormalities in minimal hepatic encephalopathy (MHE). We conducted the first study to investigate thalamic structural connectivity alterations in MHE. Methods: DTI-based probabilistic tractography was employed to determine the structural linkage between thalamus and cortical/subcortical regions in 52 cirrhotic patients [22 with MHE; 30 without MHE (NHE)], and 30 controls. We measured these thalamic connections, which included connectivity strength (CS), fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD), and then compared these among three groups. Neurocognitive assessment was also performed. Correlation analysis was conducted to investigate the relationship between neurocognitive performance and the above measurements. Classification analysis was performed to determine whether thalamic connection measurements can distinguish MHE from NHE. Results: The probabilistic tractography revealed thalamic structural connections, which were disrupted in cirrhotic patients (as reflected by a decrease in CS/FA and an increase in MD/AD/RD). Abnormal thalamic connections primarily involved prefrontal cortex, sensorimotor cortex, parietal cortex, medial temporal cortex and hippocampus, and striatum. Thalamic connectivity abnormalities deteriorated from NHE to MHE, and they were correlated with patients’ neurocognitive performance. The moderate classification accuracy was obtained using CS and MD as discriminating index. Conclusion: Our results demonstrated the altered thalamic structural connectivity involving both cortical and subcortical regions in MHE, which could be regarded as a representative of the MHE-related widespread impairments in white matter pathways. The disturbed thalamic connectivity may underlie the mechanism of cognitive deficits in MHE and may potentially be utilized as a biomarker for diagnosing MHE and in monitoring disease progression. In addition to thalamic-cortical/subcortical connections, further studies are recommended to explore the structural alterations in other white matter pathways in MHE.